RCS measurements of UAVs and their statistical analysis - Rosamilia, Massimo; Aubry, Augusto; Balleri, Alessio; Carotenuto, Vincenzo; De Maio, Antonio (Institute of Electrical and Electronics Engineers (IEEE), 2022)
This paper deals with Radar Cross Section (RCS) measurements of five small Unmanned Aerial Vehicles (UAVs) in a semi-controlled environment as a function of azimuth aspect angle, polarization, and frequency in the range 8.2-18 GHz. The experimental setup and the data pre-processing, which include coherent background subtraction, range gating procedures, and calibration, are presented. Then, a thorough statistical analysis of the measured RCSs is provided by means of the Cram´er–von Mises (CVM) distance and the Kolmogorov–Smirnov (KS) test.